Skrining Depresi pada Ibu dengan Anak Tuna Grahita Menggunakan Alat Beck Depression Inventory di Sekolah Luar Biasa Negeri C dan C1 Kota Denpasar Tahun 2014 - Kusumadjaja, Aretha Aprillya; Ardani, I Gusti Ayu Indah (E-Jurnal Medika Udayana, 2017)
The high level of children with intelectual dissability’s demand on ongoing nurture from their parents, makes not only high burden of psychological condition but also could serve as precipitating factor of depression, especially in mother who have bigger part on extra care and practical work that the child with intelectual dissabuility requires. This study examine the depression rate in mother with intelectual dissability children using Beck Depression Inventory at Sekolah Luar Biasa Negeri C and C1 Denpasar 2014. This study’s subject taken from Sekolah Luar Biasa Negeri C and C1 Denpasar started from 1st April 2014 until 31th October 2014. This study using cross-sectional descriptive methods to examine the depression rate in mother with intelectual dissability children using Beck Depression Inventory at Sekolah Luar Biasa Negeri C and C1 Denpasar 2014. Primary data is taken using Questionnaire directly from the study’s subject and already meet the inclsion criteria. The analyse based on 77mothers participating in this study revealed the depression rate in mother with intelectual dissability children mostly have minimal depression rate or normal (77,9%). With higher characteristic are educational level on senior high school graduate, married, as a housewife and range of age from 41 to 50 years old. The depression rate in mother with intelectual dissability children at Sekolah Luar Biasa C and C1 Denpasar 2014 mostly have minimal depression rate or normal. The result of the study are expected can be used as a reference of the next study to know the relationship between depression in mother with intelectual dissability children. Keyword: Maternal Depression, Depression in Mother, Intelectual Dissability, Mental Retardation, Prevalence